Structuring of particle-associated bacterial communities along the extracellular polymeric substance gradient of sinking and suspended particles in an oligotrophic, subtropical region of the western North Pacific Ocean - Ebihara, Akiko; Fukuda, Hideki; Yamada, Yosuke; Yokokawa, Taichi; Miki, Takeshi; Nagata, Toshi (Frontiers in Marine Science, 2024)
Extracellular polymeric substances, such as transparent exopolymer particles (TEP) composed of acidic polysaccharides, are important particulate organic carbon (POC) components of marine environments that affect particle dynamics and ocean carbon export. However, how polymeric substances interact with and shape bacterial communities associated with marine particles is poorly understood. This study investigated whether the composition of particle-associated bacterial communities differs between sinking and suspended particles, which differ in their polymeric substance contents, in the upper water column of the subtropical, oligotrophic Kuroshio region.Bacterial taxa likely involved in polymer degradation (Alphaproteobacteria, Gammaproteobacteria, and Bacteroidia) were enriched on sinking particles with lower TEP:POC ratio, indicating that bacterial degradation of polymeric substances promotes particle sinking by removing positively buoyant polymers. By contrast, suspended particles were increasingly enriched for Bdellovibrionota and Desulfobacterota as the TEP:POC ratio increased. These taxa, which include predatory microbes, seem to prefer polymer-rich environments with a high density of potential prey. Planctomycetota were not significantly related to the TEP:POC ratio, indicating their broad niche breadth on particles' polymeric substance contents. The results suggest that the bacterial niche differentiation associated with the particle polymeric-substance gradient shapes bacterial communities in a subtropical ocean.